The disciplined mind : what all students should understand - Gardner, Howard (New York : Simon & Schuster, 1999)
Discusses the need for educational reform, focusing on the content of an education and how it should be presented, mastered, put to use, and passed along; and uses the three examples of the theory of evolution, the music of Mozart, and the Holocaust to explore the author's call for an educational system that pursues truth, beauty, and morality.
Includes bibliographical references (p. [265]-277) and index.
Adult
Adult
Library Journal
Publisher's Weekly
Booklist
Keywords: Education -- Philosophy; Learning, Psychology of; Comprehension; Multiple intelligences; Education -- Philosophy; Psychology of learning